2022
DOI: 10.3390/tomography8030098
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Metastatic Lymph Nodes at Preoperative Staging CT in Gastric Adenocarcinoma

Abstract: Background. The aim of this study was to identify the most accurate computed-tomography (CT) dimensional criteria of loco-regional lymph nodes (LNs) for detecting nodal metastases in gastric cancer (GC) patients. Methods. Staging CTs of surgically resected GC were jointly reviewed by two radiologists, considering only loco-regional LNs with a long axis (LA) ≥ 5 mm. For each nodal group, the short axis (SA), volume and SA/LA ratio of the largest LN, the sum of the SAs of all LNs, and the mean of the SA/LA ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…In the per-patient analysis, the sum of the SAs of all LNs in the locoregional nodal groups yielded the best AUC, with a sensitivity and specificity of 65.6% and 83.7%, respectively. The authors concluded that the sum of the SAs of all LNs in staging CT scans is the most reliable predictor for both metastatic invasion of the nodal group and the presence of metastatic LNs in patients with gastric cancer [ 13 ].…”
mentioning
confidence: 99%
“…In the per-patient analysis, the sum of the SAs of all LNs in the locoregional nodal groups yielded the best AUC, with a sensitivity and specificity of 65.6% and 83.7%, respectively. The authors concluded that the sum of the SAs of all LNs in staging CT scans is the most reliable predictor for both metastatic invasion of the nodal group and the presence of metastatic LNs in patients with gastric cancer [ 13 ].…”
mentioning
confidence: 99%